Drying delay effect on physiological quality of stored annual ryegrass seeds - Eichelberger, Luiz; Maia, Manoel de Souza; Peske, Silmar Teichert; Moraes, Dario Munt de (Pesquisa Agropecuaria Brasileira, 2003)
The objective of this work was to study drying delay effect on physiological quality of annual ryegrass seeds (Lolium multiflorum Lam.), cultivar Comum-RS. Drying delay periods (0, 2, 4, 6, 8, 12, 18, 24, 36 and 48 hours) and storage periods (0, 4 and 8 months) were compared. Drying delay was performed using 18 polystyrene boxes with 24 kg of seeds each. Following, seeds were placed on a shadowy concrete floor for 12 hours, followed by a drying period in a forced air oven. Seeds retained initial germination percentage after 8-month storage period with drying delay up to 12 hours. From 6-hour drying delay, seed vigor began to be reduced after 8-month storage period. Until 4-month storage period, seed vigor was maintained with up to 11-hour drying delay. Seeds with germination percentage above 70% retained those values until 8-month storage period unrelated to drying delay period.